Predicative and sound-supporting words as a component of the specific relation - Ramil Hamitovich Mirzagitov, Damir Haydarovich Husnutdinov, Ramilya Kamilovna Sagdieva,; Karipzhanova, Gulnaz Tokenovna (Opción, 2019)
This article discusses the roles of predicative and onomatopoeic words as a component of the concretizing relationship in the Tatar literary language via descriptive-analytical research method. As a result, in syntactic terms, both onomatopoeic words and predicative words can be attributed to notional parts of speech, as they form word combinations. In conclusion, the semantic relationship between dependent and dominant components, their means of communication, require careful analysis both in functional and semantic aspects. The concretizing relation plays an important role in formation of speech